การปรับปรุงข้อบกพร่องหลักในกระบวนการขึ้นรูปโลหะ สำหรับอุตสาหกรรมรถยนต์ - คมสัน สนองพงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The economic crisis in Thailand since couples of years ago has put off the country economic situation with an impact on many industries. An automotive industry, has been effected very slightly. Besides, the automotive industry helps to uphold the employment condition of the country, referred to the high volume of labors used in the industry. Therefore, the improvement of competitive abilities, especially in quality, is very crucial. The objective of this thesis was to emphasize on the improvement of the causes of defect occurred during the machining process by using industrial engineering techniques as the following: an improvement of working standard; an improvement and modification of the machines and equipment; an improvement of a preventive manitenance system: a failure mode and effects analysis (FMEA) and an improvement of staff training program. The target of this objective was to reduce the occurrence of defect to be less than 3 percent. From problem analysis method of a sample industry, it revealed that the defect, which is frequently occurred in the manufacturing process, comprises of unstandardizable drilling hole pitch, unstandardizable drilling hole diameter, unstandardizable boring hole diameter, and oblique drilling hole. These defects are caused by some important reasons. The first reason is from the wrong performance of staff. The secon is from the damaged or ruined machines and equipments. The third is from the unstadardizable material. Final reason is from the unstandardizable operations. By following the research steps, comparing between the before and after applied techniques, it was found that percentage of defect is reduced from 9.5% to 1.8%